Antibacterial and antifungal activity of ethanol extract of Curcuma casiea (Chittagong University Journal of Biological Sciences, 2013)
DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13380 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):149-154, 2010